In the wake of Medea : neoclassical theater and the arts of destruction - Cherbuliez, Juliette, 1970- (Fordham University Press, 2020)
Through the figure of Medea, shows how important violence was for seventeenth-century French tragedy and contextualizes that violence in a longer literary and philosophical history from Ovid to Pasolini.